2009
DOI: 10.1007/s00428-009-0829-4
|View full text |Cite
|
Sign up to set email alerts
|

CpG island hypermethylation and repetitive DNA hypomethylation in premalignant lesion of extrahepatic cholangiocarcinoma

Abstract: Biliary intraepithelial neoplasia (BilIN) is the premalignant lesion of extrahepatic cholangiocarcinoma (EHC), and there are no published data regarding epigenetic changes throughout disease progression from normal biliary epithelia to BilIN to EHC. The objective of this study was to identify the occurrence of CpG island hypermethylation and repetitive DNA hypomethylation in BilIN. A total of 50 EHCs, 31 BilINs, and 31 normal cystic duct samples were analyzed for their methylation status in seven genes and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…Although the presence of global hypomethylation is considered to be a universal phenomenon across various types of cancers [14,[29][30][31], this is the first report on its presence in ESCCs and provides a fundamental piece of information. Also, it was striking that hypomethylation of Alu, but not LINE1, was present in non-cancerous background mucosae of ESCC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Although the presence of global hypomethylation is considered to be a universal phenomenon across various types of cancers [14,[29][30][31], this is the first report on its presence in ESCCs and provides a fundamental piece of information. Also, it was striking that hypomethylation of Alu, but not LINE1, was present in non-cancerous background mucosae of ESCC patients.…”
Section: Discussionmentioning
confidence: 95%
“…By aberrant promoter hypermethylation, transcription of the promoter regions of tumor suppressor genes is repressed leading to gene silencing. Subsets of CpG island loci are hypermethylated in premalignant or in situ neoplastic lesions, including extrahepatic biliary intraepithelial neoplasia [32], colon adenomas [33], gastric adenomas [34], pancreatic intraepithelial neoplasia [35], and prostatic intraepithelial neoplasia [36], although the methylation frequencies or methylation levels at each locus are generally lower in premalignant lesions than in their malignant counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial malignancies which develop through multistep carcinogenesis have demonstrated a stepwise increase of CpG island hypermethylation and a stepwise decrease of methylation levels in repetitive DNA elements with the progression of the lesion along multistep carcinogenesis, including hepatocellular carcinoma [30], gastric cancer [31], prostate cancer [32], and extrahepatic cholangiocarcinoma [33]. In contrast with these malignancies, colorectal cancers in the present study showed neither further increase of promoter CpG island hypermethylation compared with those of colon adenomas nor further decrease of LINE-1 and ALU methylation levels compared with those of colon adenomas.…”
Section: Discussionmentioning
confidence: 99%